Тюльпанная лихорадка: роман / Д. Моггак ; пер. В. Н. Соколов - Моггак Дебора (АСТ, 2017)
Экземпляры: ф.15 (20170920) / Инвентарный номер: 54139 / Цена: / Сис.шифр: И(4Вел) / Авт.знак: М 74 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44